2002
DOI: 10.1128/iai.70.4.1896-1908.2002
|View full text |Cite|
|
Sign up to set email alerts
|

The Nucleotide Sequence of Shiga Toxin (Stx) 2e-Encoding Phage φP27 Is Not Related to Other Stx Phage Genomes, but the Modular Genetic Structure Is Conserved

Abstract: In this study we determined the complete nucleotide sequence of Shiga toxin 2e-encoding bacteriophage P27, isolated from the Shiga toxin-producing Escherichia coli patient isolate 2771/97. P27 is integrated as a prophage in the chromosomal yecE gene. This integration generates identity segments of attL and attR sites with lengths of 11 nucleotides. The integrated prophage genome has a size of 42,575 bp. We identified 58 open reading frames (ORFs), each with a length of >150 nucleotides. The deduced proteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 72 publications
1
43
0
Order By: Relevance
“…All E. coli O111 strains included in those experiments carried a similar region downstream of the stx 1 gene, which is distinct from that of Stx phages present in other STEC serotypes (Unkmeir & Schmidt, 2000). Our findings confirm previous conclusions that although Stx phages share a similar morphology, a similar mode of replication and a similar genomic structure, they can be heterogeneous at the nucleotide and deduced amino acid level (Recktenwald & Schmidt, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…All E. coli O111 strains included in those experiments carried a similar region downstream of the stx 1 gene, which is distinct from that of Stx phages present in other STEC serotypes (Unkmeir & Schmidt, 2000). Our findings confirm previous conclusions that although Stx phages share a similar morphology, a similar mode of replication and a similar genomic structure, they can be heterogeneous at the nucleotide and deduced amino acid level (Recktenwald & Schmidt, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…Morphologically, this results in a replication-competent Mu-like myovirus and another dilemma for phage taxonomy. A similar siphovirus-myovirus recombinant was found in E. coli phage P27 (175). Also, Xylella fastidiosa prophages XfP1 and XfP2 combine DNA-packaging genes from lambdoid phages with tail genes from P2-like Myoviridae (187) (Fig.…”
Section: Chimeric Prophagesmentioning
confidence: 89%
“…Recktenwald and Schmidt (17) recently reported that an Stx2e-encoding phage, ø27, is integrated in yecE located in the 194͞195 segment, and that its genome structure markedly differs from either Sp5 or Sp15. Because the phage was isolated from a non-O157 strain, the finding implies that EHEC strains belonging to different lineages have acquired stx by infection with different types of Stx phages.…”
Section: Discussionmentioning
confidence: 99%